The diagnostic value of fine needle aspiration in parotid lumps - Mallon, DH (Royal College of Surgeons, 2013)
INTRODUCTION: Fine needle aspiration (FNA) is a safe and quick method of diagnosing superficial lumps, which aids preoperative planning. However, FNA of the parotid gland has not gained the widespread acceptance noted in other head and neck lumps. The aim of this study was to determine the ability of FNA of the parotid gland to differentiate benign and malignant disease, and to determine the impact on surgical outcome. METHODS: A retrospective analysis of 201 consecutive parotid operations with preoperative FNA in a large district hospital in the UK was performed. The diagnostic characteristics were calculated for benign and malignant disease, and the impact on surgical procedure was determined. RESULTS: In identifying benign disease, FNA has a sensitivity of 85% and a specificity of 76%. In detecting malignant disease, FNA has a sensitivity and specificity of 52% and 92% respectively. A false positive on FNA was associated with a higher incidence of neck dissection. CONCLUSIONS: FNA is a useful diagnostic test. However, owing to low sensitivity, it is necessary to interpret it in the context of all other clinical information.